3rd ASIA International Conference (AIC 2017) Conference Program and Abstract Book - Cheuk, Sharon; Atang, Azuriaty; Lo, May Chiun; Ramayah, T. (2017)
Rural tourism hasbeen shown to benefit local communities from the economic perspective. Digitalmarketing allows marketing information to be transmitted directly to potentialvisitors without the need for an intermediary, in a low-cost but effective way.Rural tourism destinations in Sarawak now have an opportunity to benefit from the Sarawak state government’sinitiative, the Digital Sarawak Centre of Excellence, in terms of digitalcontent creation and website maintenance. However, the current level of adoption is zero to minimal in ruraltourism destinations. This study examines the barriers towards digital marketingadoption from the perspective of rural tourism providers. Fieldwork was performed at two sites,Ba’kelalan and Long Lamai, in July 2016 and February 2017 respectively. A total of 19 respondents were interviewedin-depth. The study revealed thattourism providers currently depended on word-of-mouth or direct contact forbookings, but were willing to adopt digital marketing with the assistance ofknowledgeable parties. However, certainphysical, logistical and social constraints may have a detrimental effect onthe community’s readiness level to entertain tourists on a larger scale and mayfurther impede the overall progress of digital marketing adoption, at both theindividual and destination levels.